Pembuatan Makanan Bayi dan Anak (PMBA) Melalui Program Pawon Simbok Untuk Mencegah Stunting di Puskesmas Kramat - Nora Rahmanindar; Juhrotun Nisa; Meyliya Qudriani (Forum Kerjasama Pendidikan Tinggi, 2020)
The incidence of malnutrition, malnutrition and stunting occurs due to poor parenting styles of toddlers' mothers, the nutrition in 1000 days of life is not balanced so that the children under five are chronically malnourished. And there is no appropriateness of feeding according to the age of infants and toddlers. Pawon simbok is a demonstration of cooking complementary foods for breastfeeding according to the age of toddlers. This innovation continues until mothers with toddlers understand how to give food according to age, and reduce the number of malnutrition, malnutrition and stunting in the working area of ??the Kramat Puskesmas UPTD. In connection with this, it is necessary to increase knowledge about feeding babies and children (PMBA) through the Pawon Simbok Program to Prevent Stunting at Kramat Puskesmas in order to reduce the incidence of stunting in toddlers. So we will carry out the practice of feeding infants and children as well as health education to increase knowledge about stunting and nutrition in toddlers